Estimation of factors contributing to level differences in Japanese university decathlon athletes - Ashino, Y.; Ikuta, Y.; Kida, N. (PLOS ONE, 2023)
This study aimed to estimate the factors that cause differences in competition level based on the competition performance structure among university student decathletes in Japan. The results of factor analysis using the maximum likelihood method (Oblimin rotation), assuming a five-factor structure estimated from parallel analysis and the information criterion, revealed the following competitive performance structures: "running speed and body projection," "running endurance," "rotational throwing power," "translational throwing power," and "vertical leaping power." Some of these were similar to the competitive performance structures of the world`s top athletes, but they were found to have a unique structure: two throwing powers. The analysis results using latent rank theory allowed us to evaluate them on a seven-point scale. The calculated item reference profile, difficulty index, and discrimination index for each rank indicated that shot put and 100 and 400 m performance formed the basis of decathlon performance. In addition, high jump and pole vault, which fall under the category of "vertical leaping power," retained high difficulty and discrimination and were revealed to affect the stage of achievement of overall performance in the decathlon.